Correlation of Gender, Major, and Residence on Climate Change Anxiety of College Students - Espinola, Esmeth Capistrano; Maulion, Raianne Joy (Universitas Ahmad Dahlan, 2025)
This study assessed the climate change anxiety of college students based on gender, college major, and residence, and examined its effects. Using the Climate Change Anxiety Scale, an online survey was conducted with 369 college students. Descriptive statistics, multivariate analysis of variance, analysis of variance, and linear regression, were used to explore relationships between variables. Results revealed that females reported slightly higher climate change anxiety than males, non-science majors) reported higher levels than science majors, and students living in urban areas scored higher than students from rural areas. Among these variables, only college major showed a significant multivariate effect on climate change anxiety (p<0.05), particularly regarding functional impairment (p<0.05). This study highlights the predictive role of academic background in climate anxiety and underscores the need for educational and psychological strategies that promote climate science understanding and student mental health in the Philippines and Southeast Asia.